Dynamic Performance Characteristics of a Curved Slider Bearing Operating with Ferrofluids. (16th August 2012) - Singh, Udaya P.; Gupta, R. S.
Abstract : In the present theoretical investigation, the effect of ferrofluid on the dynamic characteristics of curved slider bearings is presented using Shliomis model which accounts for the rotation of magnetic particles, their magnetic moments, and the volume concentration in the fluid. The modified Reynolds equation for the dynamic state of the bearing is obtained. The results of dynamic stiffness and damping characteristics are presented. It is observed that the effect of rotation of magnetic particles improves the stiffness and damping capacities of the bearings.